2018
DOI: 10.1111/dar.12669
|View full text |Cite
|
Sign up to set email alerts
|

Policy‐relevant behaviours predict heavier drinking and mediate the relationship with age, gender and education status: Analysis from the International Alcohol Control Study

Abstract: International Alcohol Control survey data showed a relationship between policy-relevant behaviours and typical quantities consumed and support the likely effect of policy change (trading hours, price and restrictions on marketing) on heavier drinking. The path analysis also revealed policy-relevant behaviours were significant mediating variables between the effect of age, gender and educational status on consumption. However, this relationship is clearest in high-income countries. Further research is required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The Alcohol Environment Protocol (AEP) is one of the two tools used in the International Alcohol Control (IAC) study [1][2][3]. The AEP has been developed to allow countries to document and assess (in a comparable way) the environment, in which alcohol is sold and consumed, existing alcohol policies, levels of enforcement and document changes over time.…”
Section: Alcohol Environment Protocolmentioning
confidence: 99%
“…The Alcohol Environment Protocol (AEP) is one of the two tools used in the International Alcohol Control (IAC) study [1][2][3]. The AEP has been developed to allow countries to document and assess (in a comparable way) the environment, in which alcohol is sold and consumed, existing alcohol policies, levels of enforcement and document changes over time.…”
Section: Alcohol Environment Protocolmentioning
confidence: 99%
“…A meta-analysis of twin and adoption studies showed that about 50% of AUDs are heritable (11). The prevalence tends to be higher if alcohol is readily available, and people adopt a more permissive attitude toward heavy drinking (12,13). Individuals with low socioeconomic status are at least twice as likely to die from their disorders and prolonged heavy alcohol use than their counterparts with high socioeconomic status (14).…”
Section: Introductionmentioning
confidence: 99%
“…emphasized the affordability of alcohol as one of the sources of inequality in consumption‐pattern between high and low SES groups . In Vietnam, the availability of cheap homemade alcohol produced in rural settings and a very high proportion of unrecorded alcohol consumed, especially homemade spirit may facilitate the affordability of this cheap and strong alcohol for (heavy) drinkers from poorer families, especially those in the rural areas. In addition, the low price of beer , the most consumed recorded alcohol, may impose less financial barrier for the poorer.…”
Section: Discussionmentioning
confidence: 99%